Retroviral Restriction Factors Fv1 and TRIM5α Act Independently and Can Compete for Incoming Virus before Reverse Transcription - Passerini, Luca D. (American Society for Microbiology, 2006)
The restriction factors Fv1 and TRIM5α provide dominant blocks to retroviral infection, targeting incoming capsids at a postentry, preintegration step. They both restrict N-tropic murine leukemia virus with similar specificity yet act at different points in the viral life cycle. TRIM5α-restricted virus is usually unable to reverse transcribe, whereas Fv1-restricted virus reverse transcribes normally. Here we investigate the relationship between these two restriction factors by expressing Fv1 alleles in human cells. We demonstrate that Fv1 is able to compete with TRIM5α for virus before reverse transcription. In human cells expressing Fv1(b), N-tropic restricted virus becomes less infectious but reverse transcribes more efficiently, indicating competition between the two antiviral molecules and protection of the virus from TRIM5α by Fv1. Our findings suggest that, like TRIM5α, Fv1 interacts with virus before reverse transcription, but the consequences of this interaction are not realized until a later stage of the life cycle. We also demonstrate that Fv1 is functionally independent of TRIM5α when expressed in human cells.